2014
DOI: 10.1016/j.scitotenv.2013.07.094
|View full text |Cite
|
Sign up to set email alerts
|

Practice-based evidence informs environmental health policy and regulation: A case study of residential lead‐soil contamination in Rhode Island

Abstract: Prior to 1978, the exteriors of Rhode Island's municipal water towers were painted with lead-containing paint. Over time, this lead-containing paint either flaked-off or was mechanically removed and deposited on adjacent residential properties. Residents challenged inconsistencies across state agencies and federal requirements for collecting and analyzing soil samples. The purpose of this case study was to evaluate the efficacy of Rhode Island Department of Health (RIDOH) soil sampling regulations in determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Results are exemplified in Figure 2 for soils collected at different distances from the telephone kiosk on Dartmoor, where all heavy metals were present in the paint at relatively high concentrations but additional anthropogenic sources are absent. Here, values of EF reveal an exponential reduction for all metals to a distance of 3 to 5 m, a distribution that is characteristic of a point-source of particulate metal, like paint, rather than a diffuse one (Clark and Knudsen, 2013;Thompson et al, 2014).…”
Section: Soil Characteristics and Heavy Metal Content And Enrichmentmentioning
confidence: 82%
“…Results are exemplified in Figure 2 for soils collected at different distances from the telephone kiosk on Dartmoor, where all heavy metals were present in the paint at relatively high concentrations but additional anthropogenic sources are absent. Here, values of EF reveal an exponential reduction for all metals to a distance of 3 to 5 m, a distribution that is characteristic of a point-source of particulate metal, like paint, rather than a diffuse one (Clark and Knudsen, 2013;Thompson et al, 2014).…”
Section: Soil Characteristics and Heavy Metal Content And Enrichmentmentioning
confidence: 82%
“… 1 , 11 , 12 Contaminants tend to concentrate in low-income neighborhoods with large minority populations—although rural areas are not immune. 12 , 13 , 14 …”
Section: Measuring Soil Healthmentioning
confidence: 99%
“…Soil data from Rhode Island yards showed that lead-based paint spread more than 400 feet from nearby water towers, and often penetrated more than 12 inches below the soil surface. 14 “The heterogeneity of contaminant distribution is one of the biggest challenges,” says Hettiarachchi. “You cannot actually afford to run so many samples.”…”
Section: Measuring Soil Healthmentioning
confidence: 99%
“…The urban environment consists of various outdoor areas where children can be exposed to elevated soil Pb concentrations including public parks (Han et al, 2017;Pavilonis et al, 2021), playgrounds (Takaoka et al, 2006), and residential soils (Bradham et al, 2017;Thompson et al, 2014). Inhalation and/or ingestion of Pb-contaminated soils has been shown to be one of the most important exposure pathways in childhood (Mielke et al, 2016;Mielke & Reagan, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Pb soil contamination can be considered a function of legacy sources of Pb (i.e., lead-based paint, leaded gasoline, industrial operations) and their accumulation in urban soils (Mielke & Reagan, 1998;Han et al, 2017;Pavilonis et al, 2021). Numerous studies have identified public parks and residential soils as primary urban sources and reservoirs for accumulated lead dust (Sun et al, 2021;Thompson et al, 2014;Pavilonis et al, 2021;Mielke & Reagan, 1998;Duzgoren-Aydin et al, 2006). According to data provided by the 2007-2010 US Geological Survey Background Soil Lead Survey, the 95th and 99th percentiles for background soil Pb concentrations in the state of Pennsylvania were identified as 153 ppm and 261 ppm respectively (USEPA, 2022).…”
Section: Introductionmentioning
confidence: 99%